Development and validation of the quantification of GIZH-298, possessing in the rat blood plasma by HPLC-UF - O. G. Gribakina; R. V. Shevchenko; G. B. Kolyvanov; A. A. Litvin; P. O. Bochkov; S. S. Boyko; V. P. Zherdev (Фармакокинетика и Фармакодинамика, 2019)
He technique of quantitative determination of a new compound GIZH-298 in the rat blood plasma was developed and validated. Analysis was performed by HPLC-UV. The method was linear in the range of 100-5000 ng/ml. Recovery of GIZH-298 was 86,88 %. Limit of detection was 100 ng/ml.